Prevalence of Oculomycosis in a Tertiary Care Centre - Vijaya S. Rajmane; Mangala P. Ghatole; Sarita N. Kothadia (Al Ameen Medical College, 2011)
Objectives: The present study was undertaken to investigate the prevalence of mycotic keratitis among clinically diagnosed cases of ulcerative keratitis attending ophthalmic OPD & admitted in ward of Shri Chhatrapati Shivaji Maharaj General Hospital, Solapur from Jan 2005 to Dec 2005. Background: Mycotic keratitis has emerged to be a major ophthalmic problem since its recognition in 1879, especially in subtropical & tropical climates. Method: The patients diagnosed clinically as minor corneal abrasion, healed corneal ulcer or corneal opacity with no signs of infection was not included in this study. The corneal scrapings were processed for bacteriological and mycological examination. The material was subjected to 10% KOH mount & cultured on Sabouraud dextrose agar with & without antibiotics. Result: Out of 74 samples, 13 (17.56%) revealed hyphae in direct KOH mount and 25 (33.78%) showed fungal culture positive. Among the fungal isolates, Aspergillus was more prevalent (18.91%) followed by Fusarium spp. (5.4%) and Curvularia spp. (2.7%). Among the rare fungi causing mycotic keratitits one isolate each of Exserohilum rostratum, Colletotrichum gloeosporiodes, Bipolaris spicifera & Rhodotorula rubra were isolated in the present study.Out of 74 cases, agricultural workers 32 (43.24%) formed the major occupational group i.e.32 (43.24%) as they are more prone to trauma by vegetative matter. Conclusion: The bacteriological and mycological examination of keratitis is definitely contributory for specific management and to save the vision of the patients.